2021
DOI: 10.1186/s12962-021-00315-2
|View full text |Cite
|
Sign up to set email alerts
|

Household catastrophic health expenditure and its effective factors: a case of Iran

Abstract: Background The World Health Organization (WHO) has placed special emphasis on protecting households from health care expenditures. Many households face catastrophic health expenditures (CHEs) from a combination of economic poverty and financing the treatment of medical conditions. The present study aimed to measure the percentage of households facing catastrophic CHEs and the factors associated with the occurrence of CHEs in Shiraz, Iran in 2018. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…In a study by Ravangard et al evaluated household catastrophic health expenditure and its effective factors from Iran showed that 16.48% of studied households had faced CHEs. The higher ones facing CHEs were observed in the households living in rented houses, households with disabled members and households with children under 5 years old (7). In our study, we found that parents of patients with amino acid metabolism disorders with dietary treatment had signi cantly higher CHEs than those who had other types of IEM.…”
Section: Discussionsupporting
confidence: 45%
“…In a study by Ravangard et al evaluated household catastrophic health expenditure and its effective factors from Iran showed that 16.48% of studied households had faced CHEs. The higher ones facing CHEs were observed in the households living in rented houses, households with disabled members and households with children under 5 years old (7). In our study, we found that parents of patients with amino acid metabolism disorders with dietary treatment had signi cantly higher CHEs than those who had other types of IEM.…”
Section: Discussionsupporting
confidence: 45%
“…This review also reported that households with more children under 5 years were at risk of incurring CHE. A cross-sectional study carried out in Iran also reported that households with is the author/funder, who has granted medRxiv a license to display the preprint in (which was not certified by peer review) children under 5 had a greater risk of encountering financial burden due to health spending [71]. Both studies support the idea that children under 5 are prone to childhood illnesses and injuries and as such will require more healthcare services.…”
Section: Determinants Of Che and Impoverishment Due To Health Spendingmentioning
confidence: 83%
“…Nevertheless, to fight against health expenditures costs, WHO emphasize the use of healthcare insurance [ 25 ]. The idea of universal healthcare coverage is a working promise in developed countries but the opposite is true in developing countries [ 8 , 26 ].…”
Section: Discussionmentioning
confidence: 99%